2011
DOI: 10.1111/j.1745-3933.2011.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

The first observation of optical pulsations from a soft gamma repeater: SGR 0501+4516

Abstract: We present high-speed optical photometry of the soft gamma repeater SGR 0501+4516, obtained with ULTRACAM on two consecutive nights approximately 4 months after the source was discovered via its gamma-ray bursts. We detect SGR 0501+4516 at a magnitude of i = 24.4 ± 0.1. We present the first measurement of optical pulsations from a SGR, deriving a period of 5.7622 ± 0.0003 s, in excellent agreement with the X-ray spin period of the neutron star. We compare the morphologies of the optical pulse profile with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…This negative result is in better agreement with a magnetospheric origin interpretation, in which case the IR/optical flux is expected to be fainter for lower field strengths. Moreover, a magnetospheric scenario is more likely to explain the fact that, when detected, the observed optical emission is pulsed at the pulsar period, with pulsed fractions > 50%, i.e., higher than in soft X-rays (Kern & Martin, 2002;Dhillon et al, 2009Dhillon et al, , 2011.…”
Section: Ir/optical Emissionmentioning
confidence: 98%
“…This negative result is in better agreement with a magnetospheric origin interpretation, in which case the IR/optical flux is expected to be fainter for lower field strengths. Moreover, a magnetospheric scenario is more likely to explain the fact that, when detected, the observed optical emission is pulsed at the pulsar period, with pulsed fractions > 50%, i.e., higher than in soft X-rays (Kern & Martin, 2002;Dhillon et al, 2009Dhillon et al, , 2011.…”
Section: Ir/optical Emissionmentioning
confidence: 98%
“…For an assumed Swift J1822.3−1606 distance of 5 kpc, this implies an optical luminosity L z 4 × 10 31 erg s −1 during the outburst phase. Only very few magnetars are detected in the optical band, the only ones being 4U 0142+614, 1E 1048.1−5937, and SGR 0501+4516, all detected in the I band (see, e.g., Mignani 2011; Dhillon et al 2011). The optical flux of, e.g., 1E 1048.1−5937 during its recent flaring phase (Wang et al 2008) corresponds to an I-band luminosity L I ∼ (4 ± 2) × 10 30 erg s −1 for an assumed distance of 3 ± 1 kpc (Gaensler et al 2005).…”
Section: Radio and Optical Constraintsmentioning
confidence: 99%
“…For NH = 10 22 cm −2 (Rea et al 2009) we have converted the observed magnitudes when the X-ray luminosity is close to the quiescent level [i = 24.4 ± 0.4, u > 24.7, g > 26.9, K = 19.7 ± 0.1 (Dhillon et al 2011)] into the unabsorbed flux values. It is seen in Fig.…”
Section: Long-term Evolution Of Sgr 0501+4516mentioning
confidence: 99%